IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) MELALUI PEMBELAJARAN BERDIFERENSIASI PADA MATERI TEKS DESKRIPSI DI SMP NEGERI 7 PALEMBANG - Millenia Safitri; Juaidah Agustina (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to describe the implementation of the Teaching at the Right Level (TaRL) approach through differentiated instruction in descriptive text material for ninth-grade students at SMP N 7 Palembang. This approach takes into account students' varying abilities, interests, and learning styles. A qualitative descriptive method was used in this research, involving 36 students as subjects. The results indicate that the implementation of differentiated instruction through the TaRL approach consists of four stages: (1) Conducting an initial diagnostic assessment to map students' needs, (2) Designing differentiated lesson plans, (3) Implementing the TaRL approach through differentiated instruction in descriptive text material, and (4) Conducting reflection and evaluation. The application of this approach had a positive impact on students' learning motivation, making them more enthusiastic and active in the learning process. Adjusting the learning material based on the individual abilities and needs of students proved effective in enhancing their understanding of the material.